A new P. putida instrumental toxicity bioassay - Figueredo, Federico (2015)
Here, we present a new toxicity bioassay (CO2-TOX), able to detect toxic or inhibitory compounds in water samples, based on the quantification of Pseudomonas putida KT2440 CO2 production. The metabolically produced CO2 was measured continuously and directly in the liquid assay media, with a potentiometric gas electrode. The optimization studies were performed using as a model toxicant 3,5-DCP (3,5-dichlorophenol); later, heavy metals (Pb2+, Cu2+, or Zn2+) and a metalloid (As5+) were assayed. The response to toxics was evident after 15 min of incubation and at relatively low concentrations (e.g., 1.1 mg/L of 3,5-DCP), showing that the CO2-TOX bioassay is fast and sensitive. The EC50 values obtained were 4.93, 0.12, 6.05, 32.17, and 37.81 mg/L for 3,5-DCP, Cu2+, Zn2+, As5+, and Pb2+, respectively, at neutral pH. Additionally, the effect of the pH of the sample and the use of lyophilized bacteria were also analyzed showing that the bioassay can be implemented in different conditions. Moreover, highly turbid samples and samples with very low oxygen levels were measured successfully with the new instrumental bioassay described here. Finally, simulated samples containing 3,5-DCP or a heavy metal mixture were tested using the proposed bioassay and a standard ISO bioassay, showing that our test is more sensible to the phenol but less sensible to the metal mixtures. Therefore, we propose CO2-TOX as a rapid, sensitive, low-cost, and robust instrumental bioassay that could perform as an industrial wastewater-process monitor among other applications.